Reversible redox-responsive 1H/19F MRI molecular probes. Issue 29 (12th March 2020) - Chen, Hongming; Tang, Xiaoxue; Gong, Xuanqing; Chen, Dongxia; Li, Ao; Sun, Chengjie; Lin, Hongyu; Gao, Jinhao
Abstract : The redox-responsive manganese(ii )/(iii ) complexes serve as a pair of reversible probes for 1 H MRI and 19 F MRI of biological redox species. Abstract : Herein we report a pair of redox-responsive manganese complexes Mn(iii )/(ii )- N, N ′-bis(2-hydroxy-4-trifluoromethylbenzyl)ethylenediamine- N, N ′-diacetate (HTFBED, L1), which are water soluble and biologically interconvertible, as reversible redox-responsive probes in 1 H/ 19 F MRI for detecting and imaging biological redox species, offering a means to access valuable redox information associated with various diseases.